Testing for multigroup invariance of the perceived locus of causality in sport - Wang, C.; Pyun, D.; Kim, J.; Chatzisarantis, Nikos (Elsevier Sciences Ltd, 2009)
One popular scale in measuring motivation in sport is the perceived locus of causality (PLOC). While the scale has been widely utilized in sport, there is lack of empirical evidence to support the equivalence of the scale across diverse age groups. The Singapore government has recently initiated a new project to propel youths' participation in sport. For an effective implementation of the project, it is important to develop students' interests and motivation to continue their involvement and behavioural persistence for sport. The purpose of the study was to test the invariance of all PLOC items proposed to measure their respective factors across three age groups. A sample of 3289 students took part in the study. The results revealed that several items were perceived differently across the students in the three academic groups.